Analisis Pertumbuhan Laba Dalam Rasio Keuangan Pada Pt Semen Indonesia Tbk - Vina Arnita; Aulia Aulia; Eky Ermal Muttaqin; Suryani Suryani (Mahesa Research Center, 2021)
This research was aimed to know the effects of variable Current Ratio, Total Assets Turnover, Gross Profit Margin, dan Return on Equity could be used to predict profit growth. The data used were the financial statements. Those were the Statement of Comprehensif Income and Statement of Financial Posisition of 5 basic industry and chemicals companies listed in Indonesian Stock Exchange from 2011 2017. To test hypothesis could be used regression analysis, T-test, F-test, and classical assumption test. The result of research showed that Total Assets Turnover, Gross Profit Margin, dan Return on Equity were significant effect to predict profit growth at basic industry and chemicals companies listed in Indonesian Stock Exchange while Current Ratio werent significant effect to predict profit growth at basic industry and chemicals companies listed in Indonesian Stock Exchange.